Study of the ability of some essential oils to inhibit influenza virus neuraminidase activity. (Experimental biology, 2015)
The effect of essential oils on the neuraminidase activity of influenza viruses with different antigenic structure wasstudied. It has been established that the orange or geranium essential oils able to inhibit the enzymatic activity of the influenza virus and, consequently, are involved in inhibiting the infectious activity of influenza virus at the stage output virions from the infected cell. It is shown that the resistance of influenza strains to the action of essential oils depends from neuraminidase subtypes, which may be due to the structural features of the enzyme active site of virus protein. The use of essential oils for the prevention and treatment of influenza may be recommended after a careful study of the composition of essential oils.
Keywords: essential oils; orange; geranium; anti-virus preparations; neuraminidase; flu